Modelling and optimization of Chromium Powder Mixed EDM Parameter Effect Over the Surface Characteristics by Response Surface Methodology Approach (International Journal of Engineering Materials and Manufacture, 2018)
In this paper, an optimization of chromium powder mixed parameters effect, i.e. discharge current, pulse on time and Cr powder concentration of AISI D2 steels in Powder Mixed EDM (PMEDM) has been made. RSM has been employed to plan and analyzed the experiment. Central composite design (CCD) was chosen as the RSM design that is useful for investigating the quadratic effects. The version 8.0 of the Design Expert software was used to develop the experimental plan for RSM. A mathematical model in the form of the multiple regression equation for second order response surface with the best fittings was developed. The results identify that discharge current and pulse on time the most important parameters effect to minimize recast layer. With the topmost desirability solution, the suggested optimum parameter of discharge current is 20.12 A, pulse-on time 50.14 Âµs and 3.96 g/L powder concentration to minimize recast layer.